Star model –model of organization design and reflections of its variables and dimensions of health performance on-filed study in medical city hospital - حمود العنزي, سعد علي; عيسى, مصطفى جعفر (Journal of Economics and Administrative Sciences, 2017)
Abstract      The goal of current research to describe and diagnose the level of attention of doctors to design and regulatory dimensions, (strategic vision, organizational structure, organizational processes, business systems, personnel), and the performance of hospitals and dimensions, in six hospitals in medicine and selected a sample for research, as well as identify organizational design effect in the performance of hospitals and dimensions (efficiency, the development of human resources, patient satisfaction, achieve financial results, quality of health care). Research has focused in part theoretical on key variables to look organizational design, which has been focusing on five categories which represented, strategy and vision, organizational processes, and business systems, and personnel, organizational structure, was followed researcher quantity, which is one of the basic entrances in studies the way including social work, it comes as a result of the use of the style of the questionnaire as an essential tool in data collection.He focused on the field side of the inductive method was used for this purpose quantitative analysis of the variables of the research, exploratory and description, practically to validate the outcome of the theoretical orientations, and the sincerity of the research hypotheses. And selected the Medical City area to search being considered the latest and greatest therapeutic and educational health institution in Iraq has included the research community's senior management in the Medical City employees and managers of hospitals and doctors, as well as doctors consultants, and other doctors who fit their characteristics with the requirements of research, it has been identified sample size in the search (212) persons, where they were distributed the questionnaire and the number of questionnaires are recovered (212) questionnaire, after the researcher to make a great effort to follow doctors research sample until completing their questionnaires to fill completely. The researcher used to tackle statistical data by program (AMOS v.22) and (SPSS v.22(.     The results showed that the research hypotheses are all acceptable and positive influence, and moral, but it affects a weak level, which requires six hospitals departments of research focus on the adoption and the development and implementation of a clear practical measures regarding organizational design, because that would help to increase the influence the positive organizational design in the five dimensions of organizational performance (health care quality, patient satisfaction, and achieve financial results, and the development of human resources, and efficiency) in the six hospitals and research, and as reflected in the improvement of organizational performance for these hospitals.